Characterization of the metal/mould interface on the investment casting of gamma-TiAl - Barbosa, J. (2006)
This paper describes the evaluation of different refractory compounds – SiO2, ZrO2 and Y2O3 – as face coats of investment casting shells for c-TiAl. The effect of the different refractories on the metal–mould interaction is studied in different aspects. Experimental results include characterisation of the constituents present at the metal/ mould interface, the segregation profiles of residual elements, namely oxygen, from the interface to the inner part of the samples, the extension and microhardness of the samples external hard case and the samples surface finishing